112k views
0 votes
Find the inverse of f(x)=6/5x-3

User Hayashi
by
5.2k points

1 Answer

4 votes

For this case we must find the inverse of the following function:


f (x) = \frac {6} {5} x-3

We change
f (x) by y:


y = \frac {6} {5} x-3

We exchange the variables:


x = \frac {6} {5} y-3

We clear the variable "y":

We add 3 to both sides of the equation:


x + 3 = \frac {6} {5} y

We multiply by 5 on both sides of the equation:


5x + 15 = 6y

We divide between 6 on both sides of the equation:


y = \frac {5x + 15} {6}

We simplify:


y = \frac {5x} {6} + \frac {15} {6}\\y = \frac {5x} {6} + \frac {5} {2}

We change y for
f^( - 1) (x):


f ^ {- 1 }(x) = \frac {5x} {6} + \frac {5} {2}

Finally, the inverse function is:


f ^ {- 1} (x) = \frac {5x} {6} + \frac {5} {2}

Answer:


f ^ {- 1} (x) = \frac {5x} {6} + \frac {5} {2}

User John Rizzo
by
5.2k points